The connection (everything is interconnected) between being and knowing in Gregory Bateson: Epistemological contributions to the environmental sciences - Neto, Felipe Vieira da Cunha; de Menezes , Luis Felipe Magalhães; Bampi, Aumeri Carlos (Seven Editora, 2024)
Gregory Bateson is the author of a vast body of work, elaborating a series of concepts, reflections and deep and inspiring interdisciplinary approaches to a systemic way of knowing the world. Bateson dedicated himself to an interdisciplinary posture in his work, seeking to identify principles and elaborate concepts that could encompass different areas of knowledge and levels of existence.  However, the fact is that Gregory Bateson's work is still not widespread in the Brazilian academic environment. Thus, the objective of this study is to present some fundamental concepts present in his writings, their influence on different areas of knowledge and his integrative perspective of mind and environment, Nature and culture. Bateson contributed to Anthropology, changing paradigms and integrating the cultural and biological aspects, traditionally seen through a disciplinary prism. He also contributed to the development of Cybernetics, Psychology and Psychiatry. One of Bateson's main concepts is that of the ecology of the mind and the pattern that connects all things. DOI:https://doi.org/10.56238/sevened2024.026-032